Mudança de hábito como evolução e autocontrole no pragmatismo de Peirce - Lima, Manúcia Passos de (2008)
This research approaches the process of habit-change in the thought of Peirce (1839-1914) starting from the hypothesis that there is a strong relation between self-control and pragmatism and that habit-change takes place by a stimulus, even though vague, to use reason with the aim of reaching a coherent and admirable conduct. Peirce who was a well-known chemist with a vast experience in laboratory and owner of an eclectic mind very well trained in Logic and Philosophy is considered as one of the greatest American thinkers and the father of pragmatism. Pragmatism which is a method that aims apprenticeship and evolution e that can be used to guide thought to higher levels of clarity has a normative realm as it aims deliberate conduct, which is conscious and self-controlled. In this research it was observed that the habit conception, which is that specialization of the law of mind whereby a general idea gains the power of exciting reactions (CP 6.145) is fundamental in Peirce´s pragmatism. It was also observed that the tendency to acquiring habits as an evolution principle has in its essence a tendency to change since evolution does not happen without habit-change and vice-versa. Through evolutionary habit-change, that inspires itself in an admirable ideal, which is also under evolution, tends to rational self-control and takes place in daily practice deliberate by logic